Importance of language and number of objects in plural distinction during infancy - Pérez-Paz, Verónica Isabel; Arias-Trejo, Natalia; Alva, Elda Alicia (Anales de Psicología / Annals of Psychology, 2016)
The linguistic distinction of plurals in early developmental stages is dependent on the verbal cues provided and on the number of members in a set. More than two objects in a set facilitate plural production. Also, multiple verbal cues help understand plurals in contrast to single verbal cues such as the noun morphology alone. It remains unknown whether in a comprehension task a set with only 2 objects is associated to a plural frame, and whether the verbal cues provided play a fundamental role on the aforesaid association. Two preferential looking experiments were carried out with 24-month-old toddlers. Their ability to associate multiple plural verbal cues (E1) and morphology noun alone to a set of 2 objects (E2) was evaluated. Toddlers associated a set of 2 objects to verbal frames containing multiple cues of plurality, but not to the noun morphology alone. These findings show that, as in production, there is a certain difficulty in linguistically distinguishing a set with few objects as a representation of plural during early childhood. Nonetheless, this difficulty is diminished when multiple verbal cues are provided. This demonstrates toddlers’ ability to retrieve information from enriched syntactical frames.